Sinusoidal Harmonic Voltage Injection PWM Method for Vienna Rectifier with an LCL Filter - Park, Jin Hyuk; Lee, June Seok; Lee, Kyo Beum (IEEE Transactions on Power Electronics, 2021)
This article proposes a harmonic voltage injection pulsewidth modulation (PWM) method for a Vienna rectifier with an LCL filter. Existing PWM methods for Vienna rectifiers with full power factor can lead to resonance problems. It generates current oscillation at the resonant frequency. It is analyzed that why the resonance problem occurs in Vienna rectifier with the existing PWM methods. To solve these resonance problems, the proposed method injects a sinusoidal harmonic voltage into the sinusoidal reference voltage. The magnitude and phase of the injection voltage are determined by the power factor of the rectifier-side. Compared to other PWM methods, the proposed PWM method eliminates the possibility of resonant problems. Considering the operation characteristics of the proposed PWM method, this article suggests a design process for an LCL filter. The effectiveness and performance of the proposed PWM method and the design process for an LCL filter are verified by simulation and experiment.
Keywords: Current oscillation; Design process; Harmonic voltages; Injection voltage; Operation characteristic; Reference voltages; Resonance problem; Vienna rectifiers; LCL-filter; resonant current; third harmonic voltage injection PWM method; Vienna rectifier